Assessment of the Effectiveness Biophysical Soil and Water Conservation Structures: A Case Study of Kiramuworeda, East Wollega Zone, Ethiopia (Research and Social Study Institute, 2021)
Soil erosion is one of the most serious global environmental issues affecting agriculture and soil fertility. On a global scale, water erosion is the most common type of soil erosion in agricultural areas, reducing the soil's ability to support productive agriculture. The efficiency of biophysical soil and water conservation systems must be evaluated before solutions for limiting soil losses may be considered. To promote sustainable land use in the study area, it is critical to understand farmers' knowledge of soil and water conservation structures, as well as the factors that influence their land management practices. Farmers in the study region are well-informed about soil and water conservation structures in general, as well as their causes, indications, and the amount of their plot of land that is susceptible to soil erosion in particular. Furthermore, they feature both traditional and modern soil conservation structures that are successful. However, several impediments to implementing the Soil and Water Conservation structures were found, including a lack of finance, the small area of their land, and other socio-economic and physical aspects. Furthermore, farmers had a highly positive attitude regarding the importance of contemporary Soil and Water Conservation structures. Their awareness, on the other hand, appears to be incorrect. Because they believe that the present SWC Structure is a government-led initiative to rehabilitate highly degraded areas rather than a mechanism of soil and water conservation on agricultural land. They believe that the structures take up a huge portion of a relatively small plot of land, preventing them from properly utilizing it. As a result, it is suggested that the government's policies and strategies, as well as corrective intervention from non-governmental organizations aimed at this issue and community participation in encouraging farmers to participate in soil and water conservation practices, are critical to resolving current poverty, food insecurity, and environmental degradation in the study area.